THE EFFECTIVENESS OF REPETITION AND ROLE PLAY IN TEACHING SPEAKING - Utami, Westi Haryanti; Susilawati, Endang; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: The purpose of this research was to find out the effectiveness of Repetition and Role Play technique in teaching speaking. The study was Quasi Experimental, Nonrandomized Group Pretest-Posttest Design. The subject of the research was Year-10 students of SMK Panca Bhakti Sungai Raya in academic year 2014/2015. The sample was two classes, Accounting Class as experimental group and Hotel Management Class as control group which had 30 students of each class. Pretest and posttest were administered in both groups. The treatments were conducted three times. The data showed that the pretest mean score of both groups was similar; 56 and 56,3 for control and experimental group respectively. After the treatment, the posttest mean score of both groups was significantly different; 73,3 for experimental group, and 62,7 for control group. The data proved that repetition and role play technique had strong effect in teaching speaking. Keywords: Repetition, Role Play, Teaching Speaking Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui efektivitas teknik Pengulangan dan Bermain Peran dalam pengajaran berbicara. Penelitian ini adalah Eksperimen Semu, Desain Pretest-Posttest dengan Kelompok Non-acak. Subjek penelitian adalah siswa kelas 10 di SMK Panca Bhakti Sungai Raya pada tahun ajaran 2014/2015. Sampel penelitian terdiri dari dua kelas, yakni Kelas Akuntansi sebagai kelompok eksperimen dan Kelas Akomodasi Perhotelan sebagai kelompok kontrol dengan jumlah 30 siswa pada setiap kelas. Pretest dan posttest dilaksanakan pada kedua kelompok. Perlakukan dilakukan tiga kali. Data menunjukkan bahwa nilai rata-rata pretest siswa pada kedua kelompok serupa; 56 dan 56,3 pada masing-masing kelompok kontrol dan eksperimental. Setelah perlakuan, nilai rata-rata posttest siswa pada kedua kelompok berbeda secara signifikan, 73,3 untuk kelompok eksperimental dan 62,7 untuk kelompok kontrol. Data membuktikan bahwa teknik Pengulangan dan Bermain Peran memiliki efek kuat dalam pengajaran berbicara. Kata Kunci: Pengulangan, Bermain Peran, Pengajaran Berbicara